The role of lymphadenectomy in the surgical treatment of intrahepatic cholangiocarcinoma: A review. Issue 1 (January 2022) - Sposito, Carlo; Droz dit Busset, Michele; Virdis, Matteo; Citterio, Davide; Flores, Maria; Bongini, Marco; Niger, Monica; Mazzaferro, Vincenzo
Abstract: Cholangiocarcinoma is the second most common primary tumor of the liver. The incidence and mortality of its intrahepatic form has been increasing over the past 2 decades. Currently, the only available curative treatment for intrahepatic cholangiocarcinoma is surgical resection. There is still no prospective evidence to support neoadjuvant systemic treatments in resectable disease, while adjuvant chemotherapy with Capecitabine is currently the only recommended systemic treatment after liver resection based on the results of randomised trial. Despite the implementation of perioperative treatments and improvements in resective surgery, intrahepatic cholangiocarcinoma remains a disease characterized by high incidence of recurrence and poor long-term survival. Lymph node metastases can be found in 45–65% of patients and are one of the most impacting prognostic factors after surgical resection. Preoperative imaging is not always sufficient in assessing lymph node status, thus hepatic pedicle lymphadenectomy can be important to ensure precise staging in surgical patients. An increasing trend in performing lymph node dissection during liver resection for intrahepatic cholangiocarcinoma has been observed in the last 20 years, although its actual efficacy compared to the potential complications remains debated. The current evidence on the prognostic role of the lymph node status, its preoperative predictability, the basis for a correct hepatic pedicle lymphadenectomy and its prognostic role in the surgical treatment of intrahepatic cholangiocarcinoma are presented.